A PZT-coated cantilever for simultaneous sensing and actuating in dynamic testing of structures - Wang, Deyang (2008)
The aim of this research is to design a PZT-coated cantilever utilized as a transducer for simultaneous sensing and actuating in dynamic testing of miniature or microscale structures. In the study, the cantilever is viewed as an electromechanical system having a single electrical input port and a single mechanical output port. The relationship between the input electrical variables and output mechanical variables is then described by a two by two matrix. This matrix, termed as transduction matrix, completely characterizes the forward actuating and backward sensing functions of the cantilever transducer. Utilizing the transduction matrix, the mechanical impedance at the output port can be evaluated from the electrical impedance measured at the input port. As such, the cantilever transducer performs both actuating and sensing simultaneously in a dynamic testing of structures.